ANALISIS UJI PENETRASI PADA SISTEM MANAJEMEN DATA SUMBER TERBUKA CKAN MENGGUNAKAN METODE NATIONAL INSTITUTE OF STANDARDS AND TECHNOLOGY SPECIAL PUBLICATION (NIST SP 800-115) - Dzaki Anmaris Harahap (2023)
The development of information technology has now spread to remote parts of Indonesia, both villages, sub-districts, districts and cities have started to have divisions that implement information dissemination systems to the public using websites and one of the parties responsible for information dissemination services. It is important to ensure the confidentiality and security of information must be maintained from threats and danger. In this study there are system problems that may have security holes. Data leaks are caused by security holes that were not detected in the system and then not handled properly, allowing other people to directly enter the system. The reporting phase will describe the results of the vulnerabilities found, the level of severity, and provide instructions on how to mitigate the vulnerabilities that have been found. To maintain system security, the IT team should reconfigure the system, so that the vulnerability to incoming attacks can be overcome. Identification of vulnerabilities in the open source data management system Ckan the Bandung City Diskominfo website using the methodNational Institute of Standards and Technology Special Publicaiton 800-115.